Illustrated theatre production guide - Holloway, John (2010)
Contiene: Theatre types. properties of the proscenium theatre. Rigging. Ropes and knot tying. soft goods. Electricity. Power distribution. Dimmers and lighting control. photometrics and hanging the lights. Operating a followspot. Sound. Computer programs for theatre. Stage management. Hardware, fabrics, adhesives, and other Theatrical supplies